Catalogue of source mechanisms and overview of present-day stress fields in the western region of the Africa–Eurasia plate boundary - Ousadou, Farida; Ayadi, Abdelhakim; Bezzeghoud, Mourad (Frontiers in Earth Science, 2024)
Complex deformation is observed along the plate boundary between the Africa and Eurasia plates, this complexity is highlighted by the faulting mechanism changing from normal faulting at the Mid-Atlantic Ridge to thrust and strike-slip faulting in the Ibero-Maghreb region (Iberia, Morocco, Algeria and Tunisia). The geodynamics of the study area shows the occurrence of NW‒SE convergence between the two plates, with anticlockwise rotation. An updated scheme of the pattern of the tectonic stress direction from the Azores Archipelago to the Tunisian Atlas is presented, along with the analysis of the principal stress axis orientations (Shmax = σ1, Shmin = σ3) from the inversion of fault plane solutions. We used a catalogue of 557 fault plane solutions with only main shocks without considering the related aftershock solutions for the period from 1931 to 2020. This study complements previous work limited to Algeria and eastern Morocco by inverting earthquake mechanisms of aftershock sequences of strong events that occurred in Al Hoceima (Morocco), El Asnam, Chenoua-Tipasa, Zemmouri and Constantine (Algeria). The present work includes the area from Tunisia to the Mid-Atlantic Ridge. The inversion considers only the earthquake mechanisms of events 4.0≤M≤8.4, excluding the aftershocks of strong events. We used the Slickenside analysis package of Michael’s method. The stress field we obtained shows an extensional regime in the Mid-Atlantic Ridge, Terceira Ridge and Azores Islands and a strike-slip regime along the Gloria Fault, Gorringe Bank, and Gulf of Cadiz, to southern Spain. The same regime is also observed in the Rif and Alboran Sea. The stress regime becomes compressional in western Algeria, with strike-slip in eastern and southern Tunisia and an exception in northern Tunisia, where the stress exhibits a reverse rupture process. This study leads us to propose a new sketch of the present stress field along the western part of the Eurasia–Africa plate boundary.